Is voluntary disclosure of environmental performance associated with actual environmental performance? Evidence from Victorian local governments, Australia. Issue 2 (2nd April 2016) - Oates, Grainne; Moradi-Motlagh, Amir
ABSTRACT: This article identifies the level of voluntary disclosure of environmental performance of 76 Victorian local governments in Australia, and examines whether superior environmental performers with higher diversion rates disclose more information on their environmental performance. To better capture the rate of disclosures of environmental commitments of sample city councils, a content analysis index based on the environmental section of the Global Reporting Initiative guidelines is developed. The results indicate that the level of environmental disclosure among Victorian local governments is very low, with an average score of only 13.72 out of 100. In addition, the results reveal a positive association between environmental disclosure and underlying environmental performance, as predicted by voluntary disclosure theory.